2020
DOI: 10.3390/ijms21020402
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 Activation by Honokiol Decreases Unilateral Ureteral Obstruction-Induced Renal Inflammation and Fibrosis via Regulation of Mitochondrial Dynamics and the Renal NF-κB-TGF-β1/Smad Signaling Pathway

Abstract: Renal fibrosis is a common feature of all progressive chronic kidney diseases. Sirtuin 3 (SIRT3) is one of the mitochondrial sirtuins, and plays a role in the regulation of mitochondrial biogenesis, oxidative stress, fatty acid metabolism, and aging. Recently, honokiol (HKL), as a pharmaceutical SIRT3 activator, has been observed to have a protective effect against pressure overload-induced cardiac hypertrophy by increasing SIRT3 activity. In this study, we investigated whether HKL, as a SIRT3 activator, also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…For instance, Honokiol is one of the most studied SIRT3 activators and is a natural lignan derived from the bark of Magnolia. Honokiol could increase SIRT3 expression and deacetylation activity, which have a favorable effect on heart disease 16 , 137 , renal disease 173 , surgery/anesthesia-induced cognitive decline 174 and Vitiligo 175 . For heart disease, Honokiol activation of SIRT3 further decreases the acetylation levels of MnSOD2 and OSCP, resulting in improved mitochondrial rate of oxygen consumption and inhibition of ROS synthesis.…”
Section: Targeting Sirt3 For Potential Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Honokiol is one of the most studied SIRT3 activators and is a natural lignan derived from the bark of Magnolia. Honokiol could increase SIRT3 expression and deacetylation activity, which have a favorable effect on heart disease 16 , 137 , renal disease 173 , surgery/anesthesia-induced cognitive decline 174 and Vitiligo 175 . For heart disease, Honokiol activation of SIRT3 further decreases the acetylation levels of MnSOD2 and OSCP, resulting in improved mitochondrial rate of oxygen consumption and inhibition of ROS synthesis.…”
Section: Targeting Sirt3 For Potential Therapiesmentioning
confidence: 99%
“…This makes it possible for Honokiol to contribute to adjuvant therapy of chemotherapy 137 . In renal disease, Honokiol stimulates SIRT3 activity to block the NF-κB-TGF- β1/Smad regulated inflammation and fibrosis signaling in renal fibrosis mice model 173 . Surprisingly, Honokiol can ameliorate surgery-induced or anesthesia-induced cognitive decline in mice via SIRT3 activation mediating ROS elimination and apoptosis inhibition 174 .…”
Section: Targeting Sirt3 For Potential Therapiesmentioning
confidence: 99%
“…Indeed, it has been shown that Honokiol (2-(4-hydroxy-3-prop-2-enyl-phenyl)-4-prop-2-enyl-phenol, HKL) is able to stimulate the activity of Sirtuin 3 (SIRT3), which sequentially mediates the activation of OPA1 and decreases DRP1 expression, restoring the correct mitochondrial fusion and fission dynamics and normal mitochondrial shape and function. Thus, targeting mitochondrial dynamics can be a novel therapeutic approach for the treatment of acute or chronic kidney diseases [ 31 ].…”
Section: Mitochondrial Plasticity and Cell Signaling: A Two-way Interactionmentioning
confidence: 99%
“…In the same way, sirtuin 3 (SIRT3) is a deacetylase protein mainly localized in mitochondria, involved in the regulation of mitochondrial biogenesis and dynamics 95,96 . SIRT3 protein levels are decreased in UUO‐OKs 92 . Meanwhile, the upregulation of SIRT3 expression in UUO‐OKs helps to reduce mitochondrial fragmentation since SIRT3 activates Opa1 92 .…”
Section: Mitochondrial Dysfunction In the Uuo Modelmentioning
confidence: 99%